The Aberrant Gene-End Transcription Signal of the Matrix M Gene of Human Parainfluenza Virus Type 3 Downregulates Fusion F Protein Expression and the F-Specific Antibody Response In Vivo - Lingemann, Matthias (J Virol, 2015)
Human parainfluenza virus type 3 (HPIV3), a paramyxovirus, is a major viral cause of severe lower respiratory tract disease in infants and children. The gene-end (GE) transcription signal of the HPIV3 matrix (M) protein gene is identical to those of the nucleoprotein and phosphoprotein genes except that it contains an apparent 8-nucleotide insert. This was associated with an increased synthesis of a readthrough transcript of the M gene and the downstream fusion (F) protein gene. We hypothesized that this insert may function to downregulate the expression of F protein by interfering with termination/reinitiation at the M-F gene junction, thus promoting the production of M-F readthrough mRNA at the expense of monocistronic F mRNA. To test this hypothesis, two similar recombinant HPIV3 viruses from which this insert in the M-GE signal was removed were generated. The M-GE mutants exhibited a reduction in M-F readthrough mRNA and an increase in monocistronic F mRNA. This resulted in a substantial increase in F protein synthesis in infected cells as well as enhanced incorporation of F protein into virions. The efficiency of mutant virus replication was similar to that of wild-type (wt) HPIV3 both in vitro and in vivo. However, the F-protein-specific serum antibody response in hamsters was increased for the mutants compared to wt HPIV3. This study identifies a previously undescribed viral mechanism for attenuating the host adaptive immune response. Repairing the M-GE signal should provide a means to increase the antibody response to a live attenuated HPIV3 vaccine without affecting viral replication and attenuation. IMPORTANCE The HPIV3 M-GE signal was previously shown to contain an apparent 8-nucleotide insert that was associated with increased synthesis of a readthrough mRNA of the M gene and the downstream F gene. However, whether this had any significant effect on the synthesis of monocistronic F mRNA or F protein, virus replication, virion morphogenesis, and immunogenicity was unknown. Here, we show that the removal of this insert shifts F gene transcription from readthrough M-F mRNA to monocistronic F mRNA. This resulted in a substantial increase in the amount of F protein expressed in the cell and packaged in the virus particle. This did not affect virus replication but increased the F-specific antibody response in hamsters. Thus, in wild-type HPIV3, the aberrant M-GE signal operates a previously undescribed mechanism that reduces the expression of a major neutralization and protective antigen, resulting in reduced immunogenicity. This has implications for the design of live attenuated HPIV3 vaccines; specifically, the antibody response against F can be elevated by “repairing” the M-GE signal to achieve higher-level F antigen expression, with no effect on attenuation.